Correspondence of the Questionnaire to the Needs of Parents During Hospitalization of Child. Expert evaluation - Miķelsone, Madara; Renigere, Ruta; Gulbe, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Needs of parents during hospitalization of a child, during the health care process, are connected with the interaction of multilevel environment in the hospital setting. Created expert evaluation questionnaire and performed research serve as a basis for creation of the activity research questionnaire for parents of children and nurses employed in the health care field using acquired data. To heighten validity of the obtained data during each cycle of data analysis triangulated data acquisition methods were used. During research of the needs of parents during hospitalization of their child following methods of triangulation were used: data triangulation – quantitative and qualitative data obtained during research; sources: child’s parents and nurses; triangulation of researchers – author of the dissertation, scientific head of the dissertation, experts; triangulation of theories – sustainability/sustainable development, ecology of human development, holistic health care model, system model; triangulation of methods – questionnaires, expert evaluations, analysis of qualitative data and thematic qualitative analysis. During research the strategy of triangulation contains use of several sources of information. Relatively autonomous research methods give purposeful answers to the research questions on needs of parents during hospitalization of a child. Data obtained during activity research indicate ability of the parents and health care teams to satisfy their needs.